High-wear-resistance transparent MOPP composite label film base material and preparation method thereof
By adding polytetrafluoroethylene particles, silica and graphene oxide to the unidirectional stretched polypropylene film, and using low-temperature stretching and high-temperature stretching, a highly wear-resistant transparent MOPP composite label film substrate was prepared. The problem of degradation of wear resistance and transparency of polypropylene films is solved, and the material has high wear resistance and transparency are achieved.
Patent Information
- Application Number
- CN202411562376.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, there is a problem that the wear resistance and transparency of the unidirectional tensile polypropylene films are reduced during use.
Using a method for preparing a highly wear-resistant transparent MOPP composite label film substrate, including polypropylene masterbatch, polytetrafluoroethylene particles, silica and graphene oxide, through specific mass ratios and process steps, such as low temperature stretching and high temperature stretching to form a material with high wear resistance and transparency.
The wear resistance and transparency of polypropylene materials are improved, the material's oxidation resistance is enhanced, the problem of decreasing wear resistance and transparency is solved, and the dimensional stability and weather resistance of the material are improved.
Smart Images

Figure CN119431959A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic material processing, in particular to a method for preparing a preform containing fillers, and in particular to a highly wear-resistant transparent MOPP composite label film substrate and a method for preparing the same. Background Art
[0002] MOPP is uniaxially stretched polypropylene film, which refers to a polypropylene film that is stretched in only one direction. Due to the uniaxial stretching, the film has higher strength in the stretching direction and can still maintain stable performance at high temperatures, and is not easy to deform or break.
[0003] Using recycled polypropylene masterbatch for film preparation can significantly reduce the mining and production of new plastic raw materials, thereby saving a lot of energy resources and reducing the pollution of waste polypropylene to the environment. This helps to protect natural resources such as soil and water sources and maintain ecological balance.
[0004] In the packaging industry, especially in the packaging of food, medicine and other industries, there are high requirements for the wear resistance of materials. The uniaxially oriented polypropylene film needs to be treated with wear resistance to meet the wear resistance requirements and ensure that the product is not damaged during transportation and storage.
[0005] Existing wear-resistant treatment mainly uses surface coating treatment and wear-resistant agent blending modification, but a large number of unsaturated bonds will be mixed in the wear-resistant treatment process, and the unsaturated bonds will cause the uniaxially stretched polypropylene film to denature during long-term use, making the surface of the uniaxially stretched polypropylene film yellow and the strength weakened. In addition, the film prepared from recycled polypropylene masterbatch will reduce the strength and toughness of the polypropylene masterbatch due to the treatment during the recycling process, affecting the wear resistance and transparency of the uniaxially stretched polypropylene film.
[0006] Therefore, it is necessary to improve the method for preparing the uniaxially stretched polypropylene film in the prior art to solve the above problems. Summary of the invention
[0007] The present invention overcomes the deficiencies of the prior art and provides a highly wear-resistant and transparent MOPP composite label film substrate and a preparation method thereof, aiming to solve the defects of the prior art that the wear resistance and transparency of the uniaxially stretched polypropylene material decrease during use.
[0008] To achieve the above object, the technical solution adopted by the present invention is: a highly wear-resistant transparent MOPP composite label film substrate, comprising: component A, component B and component C, wherein:
[0009] Component A is: polypropylene masterbatch;
[0010] Component B includes: polytetrafluoroethylene particles, silicon dioxide and graphene oxide, wherein the mass ratio of the polytetrafluoroethylene particles, the silicon dioxide and the graphene oxide is: 15-20:15:20:5-10;
[0011] Component C includes: a coupling agent, a lubricant, a nucleating agent and a stabilizer, wherein the mass ratio of the coupling agent, the lubricant, the nucleating agent and the stabilizer is: 4-8: 1-2: 3-5: 2-3;
[0012] The mass ratio of the A component, the B component and the C component is 60-70:25-35:5-10.
[0013] In a preferred embodiment of the present invention, the particle diameter of the polypropylene masterbatch is 0.1-1 mm, the particle diameter of the polytetrafluoroethylene particles is 0.1-10 μm, the particle diameter of the silicon dioxide is 400-500 nm, and the particle diameter of the graphene oxide is 2-4 μm.
[0014] In a preferred embodiment of the present invention, the coupling agent is aminopropyltriethoxysilane, the lubricant is zinc stearate, the nucleating agent is dibenzylidene sorbitol, and the stabilizer is calcium stearate.
[0015] To achieve the above object, the second technical solution adopted by the present invention is: a method for preparing a highly wear-resistant transparent MOPP composite label film substrate, comprising the following steps:
[0016] S1: Sprinkle silica particles into graphene oxide solution, and stir for 4-6 hours by ultrasonic treatment, keep the temperature at 60-80°C during stirring, and take out and dry to obtain graphene oxide / silicon dioxide composite particles;
[0017] S2: placing the polypropylene masterbatch into a reactor and heating it to 160-165° C. for 1-2 hours to obtain a polypropylene copolymer;
[0018] S3: adding the graphene oxide / silicon dioxide composite particles, polytetrafluoroethylene particles, coupling agent, lubricant, nucleating agent and stabilizer in S1 into a reaction kettle, the reaction temperature is 320-330° C., the reaction time is 4-6 hours, and a polypropylene mixed material is obtained;
[0019] S4: stretching and shaping the polypropylene mixed material in S3 to obtain a highly wear-resistant and transparent MOPP composite label film substrate.
[0020] In a preferred embodiment of the present invention, the mass fraction of graphene oxide in the graphene oxide solution in S1 is 1-3%, the graphene oxide solution also includes a coupling agent, the mass fraction of the coupling agent is 0.1%-0.5%, and the solvent of the graphene oxide solution is dimethyl sulfoxide.
[0021] In a preferred embodiment of the present invention, the frequency of the ultrasonic treatment in S1 is 40-60 kHz.
[0022] In a preferred embodiment of the present invention, the gas pressure in the reactor in S2 is 3.4-3.6 MPa, and the gas pressure in the reactor in S3 is 0.8-1 MPa.
[0023] In a preferred embodiment of the present invention, during stretching in S4, low-temperature stretching is first performed for 5-7 minutes and then high-temperature stretching is performed for 10-15 minutes, the low-temperature stretching temperature is 60-80°C, the high-temperature stretching temperature is 135-145°C, and the stretching directions of the low-temperature stretching and the high-temperature stretching are consistent.
[0024] In a preferred embodiment of the present invention, the stretching ratio during low-temperature stretching is 1:2-3, and the stretching ratio during high-temperature stretching is 1:5-7.
[0025] In a preferred embodiment of the present invention, the heat setting temperature in S4 is 120° C., and the heat setting time is 10-12 minutes.
[0026] The present invention solves the defects existing in the background technology and has the following beneficial effects:
[0027] (1) The present invention provides a highly wear-resistant and transparent MOPP composite label film substrate, comprising a polypropylene masterbatch, polytetrafluoroethylene particles, silicon dioxide and graphene oxide. The silicon dioxide and graphene oxide have high strength and high hardness, and the polytetrafluoroethylene particles have lubricity. Both have good inertness. Compared with the uniaxially stretched polypropylene material in the prior art, the present invention can increase the wear resistance of polypropylene while ensuring the transparency of polypropylene, and make the material have antioxidant ability, thereby solving the problem of the uniaxially stretched polypropylene material in the prior art having a decrease in wear resistance and transparency during use.
[0028] (2) In the present invention, the polypropylene mixed material is first subjected to low-temperature stretching and then to high-temperature stretching. The low-temperature stretching reduces bubbles and voids inside the material, and the high-temperature stretching allows the molecular chains of the material to be arranged and oriented more effectively at a higher temperature. Compared with the prior art, the dimensional stability of the material can be improved, the residual stress can be reduced, the crystallinity and orientation of the material can be improved, the wear resistance and transparency of the material can be improved, and the material can resist oxidation with its uniform and tight texture, thereby improving its antioxidant properties.
[0029] (3) In the present invention, polytetrafluoroethylene has good film-forming properties and chemical stability, the nanosheet structure of graphene oxide can be uniformly dispersed in the polytetrafluoroethylene matrix to form an effective reinforcement phase, and the silicon dioxide particles fill the gaps in the polytetrafluoroethylene / graphene oxide system. Compared with the prior art, the mechanical properties of the polytetrafluoroethylene matrix are improved, the density and uniformity of the material are improved, the bonding between polytetrafluoroethylene and polypropylene can be enhanced, the oxidation resistance of the material can be improved, and the weather resistance is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 It is a method step diagram of a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0034] A highly wear-resistant transparent MOPP composite label film substrate, comprising: component A, component B and component C, wherein:
[0035] Component A is: polypropylene masterbatch;
[0036] Component B includes: polytetrafluoroethylene particles, silicon dioxide and graphene oxide, and the mass ratio of polytetrafluoroethylene particles, silicon dioxide and graphene oxide is: 15-20:15:20:5-10;
[0037] Component C includes: coupling agent, lubricant, nucleating agent and stabilizer, and the mass ratio of coupling agent, lubricant, nucleating agent and stabilizer is: 4-8: 1-2: 3-5: 2-3;
[0038] The mass ratio of component A, component B and component C is 60-70:25-35:5-10.
[0039] Silicon dioxide and graphene oxide have high strength and hardness, polytetrafluoroethylene particles have lubricity, and both have good inertness. They can increase the wear resistance of polypropylene while ensuring the transparency of polypropylene, and make the material have antioxidant ability, thus solving the defects of the prior art that the wear resistance and transparency of the uniaxially stretched polypropylene material decrease during use.
[0040] The particle diameter of polypropylene masterbatch is 0.1-1mm, the particle diameter of polytetrafluoroethylene particles is 0.1-10μm, the particle diameter of silicon dioxide is 400-500nm, and the particle diameter of graphene oxide is 2-4μm. The addition of polytetrafluoroethylene particles helps to improve the glossiness of polypropylene mixed materials and make their appearance more beautiful.
[0041] PTFE particles have excellent lubricity and a low coefficient of friction. When these fine particles are evenly dispersed in the substrate, they can reduce friction within the material, thereby improving wear resistance. Although silica particles have a higher hardness, they have a smaller particle size and can be evenly dispersed, which helps to increase the hardness of the material without excessively affecting transparency. Silica and graphene oxide have good chemical stability and weather resistance. They can protect the material from ultraviolet rays and other environmental factors, thereby extending the service life of the material. Particles of different particle sizes can optimize the dispersion and compatibility of the material. Smaller PTFE particles and silica particles can better be compatible with the polypropylene substrate to form a uniform composite material, while larger polypropylene masterbatch particles help maintain the overall structure and processing performance of the material.
[0042] Polytetrafluoroethylene has good film-forming properties and chemical stability. The nanosheet structure of graphene oxide can be evenly dispersed in the polytetrafluoroethylene matrix to form an effective reinforcement phase. The high specific surface area and strong interface interaction of graphene oxide help to improve the mechanical properties of the polytetrafluoroethylene matrix. Nano-scale silicon dioxide particles can further fill the gaps in the polytetrafluoroethylene / graphene oxide system to improve the density and uniformity of the material. The addition of silicon dioxide also helps to improve the dispersibility of graphene oxide in polytetrafluoroethylene and prevent the agglomeration of graphene oxide. The oxygen-containing functional groups (such as hydroxyl, carboxyl, etc.) on the surface of graphene oxide can interact with the polytetrafluoroethylene molecular chain to form a strong interface bond, improve the overall performance of the composite material, and can enhance the bond between polytetrafluoroethylene and polypropylene.
[0043] The coupling agent is aminopropyl triethoxysilane, the lubricant is zinc stearate, the nucleating agent is dibenzylidene sorbitol, and the stabilizer is calcium stearate. Aminopropyl triethoxysilane improves the compatibility and bonding between inorganic fillers (such as silica and graphene oxide) and organic polypropylene substrates, and bridges two materials of different properties by forming chemical bonds, thereby enhancing the mechanical properties and wear resistance of the material. Zinc stearate reduces friction and wear of the material during processing, reduces energy consumption, and helps to improve the surface quality of the product. Dibenzylidene sorbitol promotes the crystallization of polypropylene as a nucleation point, resulting in more uniform and refined crystallization. The refined crystal structure helps to reduce the light scattering of the material, thereby improving transparency, and improving the rigidity, heat deformation temperature and surface gloss of the material. Calcium stearate protects the material from the influence of heat, light, oxygen and other factors, prolongs the service life of the material, and improves weather resistance. Calcium stearate can also be used as a halogen absorber to prevent residual catalysts in polypropylene from adversely affecting color and stability.
[0044] like Figure 1 As shown, in order to achieve the above-mentioned purpose, the second set of technical solutions adopted by the present invention is: a method for preparing a highly wear-resistant transparent MOPP composite label film substrate, comprising the following steps:
[0045] S1: Sprinkle silica particles into graphene oxide solution, and stir for 4-6 hours by ultrasonic treatment, keep the temperature at 60-80°C during stirring, and take out and dry to obtain graphene oxide / silicon dioxide composite particles;
[0046] S2: Put the polypropylene masterbatch into the reactor and heat it to 160-165℃ for 1-2 hours to obtain the polypropylene copolymer; accurately control the heating temperature and time to ensure that the polypropylene masterbatch is completely melted and forms a uniform copolymer. This helps to improve the processing performance of the material and the uniformity of the final product, thereby improving transparency and wear resistance.
[0047] S3: Add the graphene oxide / silicon dioxide composite particles, polytetrafluoroethylene particles, coupling agent, lubricant, nucleating agent and stabilizer in S1 into a reactor, the reaction temperature is 320-330° C., the reaction time is 4-6 hours, and a polypropylene mixed material is obtained.
[0048] S4: The polypropylene mixed material in S3 is stretched and then shaped to obtain a highly wear-resistant transparent MOPP composite label film substrate. Through stretching and shaping, the molecular structure of the material is oriented, which helps to improve the mechanical properties of the material, including wear resistance and tear resistance.
[0049] The mass fraction of graphene oxide in the graphene oxide solution in S1 is 1-3%, the graphene oxide solution also includes a coupling agent, the mass fraction of the coupling agent is 0.1%-0.5%, and the solvent of the graphene oxide solution is dimethyl sulfoxide.
[0050] The ultrasonic treatment frequency in S1 is 40-60kHz. Ultrasonic treatment and temperature control help the silica particles to be evenly dispersed in the graphene oxide solution to form uniform composite particles. This uniform dispersion enhances the mechanical properties of the material and improves wear resistance. By adding graphene oxide / silicon dioxide composite particles to polypropylene masterbatch, the mechanical properties of the composite material, such as strength, stiffness and wear resistance, can be significantly improved. This helps to compensate for the weakening of toughness of recycled polypropylene masterbatch caused by multiple processing.
[0051] The air pressure in the reactor in S2 is 3.4-3.6MPa, and the air pressure in the reactor in S3 is 0.8-1MPa. During the heating and melting process of the polypropylene masterbatch, the higher air pressure helps to improve the melt quality of the polypropylene. The high pressure environment can promote the movement of the polypropylene molecular chains, thereby facilitating the uniform melting and mixing of the polypropylene. The high pressure can also increase the material density in the reactor, which helps to closely arrange the polypropylene molecular chains, improve the crystallinity and density of the copolymer, and thus improve the wear resistance and transparency of the material. After adding the graphene oxide / silicon dioxide composite particles and other additives, reducing the air pressure helps to promote the release of gas, reduce bubbles and defects in the material, and thus improve the transparency and surface quality of the material. The lower air pressure also helps to control the viscosity and fluidity of the polypropylene mixed material, making it easier to form and stretch in subsequent processing steps, and helps to improve the uniformity and consistency of the material.
[0052] During stretching in S4, low-temperature stretching is first used for 5-7 minutes and then high-temperature stretching is performed for 10-15 minutes. The low-temperature stretching temperature is 60-80°C, and the high-temperature stretching temperature is 135-145°C. The stretching directions of low-temperature stretching and high-temperature stretching are consistent. The stretching ratio during low-temperature stretching is 1:2-3, and the stretching ratio during high-temperature stretching is 1:5-7.
[0053] Low temperature stretching helps the material to deform moderately without causing excessive relaxation or cracking of the material. This step can produce a certain arrangement of the material's molecular chains at a lower temperature, preparing for subsequent high temperature stretching. Low temperature stretching can reduce defects inside the material, such as bubbles and voids, thereby improving the transparency and uniformity of the material. High temperature stretching can allow the material's molecular chains to align and orient more effectively at higher temperatures, thereby improving the material's strength and wear resistance. Stretching at high temperatures also helps to further improve the material's dimensional stability, because the material is more likely to flow and fill the fine parts of the mold at high temperatures, reducing residual stress.
[0054] Stretching at a lower temperature helps to initially induce the separation of the lamellae and form an initial microporous structure. This process helps to optimize the arrangement and regularity of the lamellae, reduce internal scattering centers, and lay the foundation for subsequent transparency improvement. Subsequently, stretching at a high temperature causes chain disentanglement so that some tie chains are no longer bound. They may form new bridges and further refine the microporous structure. At the same time, high-temperature stretching can also promote the rearrangement and orientation of molecular chains, reduce internal defects, and thus improve the transparency of the product. Stretching at low temperature first and then at high temperature can effectively optimize the microporous structure and lamellae arrangement, reduce scattering centers, and improve the transparency of the product.
[0055] Stretching at a lower temperature initially enhances the density and strength of the material. The initial bridges and holes formed serve as stress dispersion points, reducing local stress concentration and improving the wear resistance of the material. High-temperature stretching further enhances the mechanical properties and wear resistance of the material. The more stable and thicker bridge structure formed during the hot stretching process provides good support and can effectively disperse and transfer stress when subjected to external forces.
[0056] The heat setting temperature in S4 is 120°C and the heat setting time is 10-12 minutes. The heat setting step helps to fix the molecular chain structure of the material, ensuring that the material maintains its improved physical properties after cooling. Heat setting can also further reduce the internal stress inside the material, improve the weather resistance and stability of the material, and enable it to maintain its performance under different environmental conditions.
[0057] Embodiment 1
[0058] This embodiment prepares a highly wear-resistant transparent MOPP composite label film substrate, and the preparation process is as follows:
[0059] S1: 12.5 parts by mass of silicon dioxide particles with a particle size of 450 nm are sprinkled into a graphene oxide solution, wherein the mass fraction of graphene oxide in the graphene oxide solution is 2%, and the particle size of graphene oxide is 3 μm. The graphene oxide solution also includes aminopropyltriethoxysilane, and the mass fraction of aminopropyltriethoxysilane is 0.3%. The solvent of the graphene oxide solution is dimethyl sulfoxide, and ultrasonic treatment and stirring are carried out for 5 hours. The ultrasonic treatment frequency is 50 kHz, and the temperature during the stirring process is maintained at 70°C. After taking out and drying, graphene oxide / silicon dioxide composite particles are obtained, and the mass of graphene oxide in the obtained graphene oxide / silicon dioxide composite particles is 5 parts.
[0060] S2: 55 parts by weight of polypropylene masterbatch with a particle size of 0.1 mm was placed in a reactor, heated at a temperature of 165° C., the gas pressure in the reactor was 3.5 MPa, and the heating time was 1.5 h to obtain a polypropylene copolymer;
[0061] S3: adding the graphene oxide / silicon dioxide composite particles in S1, 12.5 parts by weight of polytetrafluoroethylene particles with a particle size of 10 μm, 2 parts by weight of aminopropyltriethoxysilane, 0.6 parts by weight of zinc stearate, 1 part by weight of dibenzylidene sorbitol and 1 part by weight of calcium stearate into a reactor, the reaction temperature is 325° C., the reactor pressure is 0.9 MPa, the reaction time is 5 hours, and a polypropylene mixed material is obtained;
[0062] S4: The polypropylene mixed material in S3 is first stretched at low temperature for 5 minutes and then stretched at high temperature for 12 minutes. The low temperature stretching temperature is 70°C and the high temperature stretching temperature is 140°C. The stretching directions of the low temperature stretching and the high temperature stretching are consistent. The stretching ratio during low temperature stretching is 1:2.5 and the stretching ratio during high temperature stretching is 1:6. After stretching, heat setting is performed at a heat setting temperature of 120°C and a heat setting time of 11 minutes to obtain a highly wear-resistant transparent MOPP composite label film substrate.
[0063] Embodiment 2
[0064] This embodiment prepares a highly wear-resistant transparent MOPP composite label film substrate, and the preparation process is as follows:
[0065] S1: 12.5 parts by mass of silicon dioxide particles with a particle size of 450 nm are sprinkled into a graphene oxide solution, wherein the mass fraction of graphene oxide in the graphene oxide solution is 2%, and the particle size of graphene oxide is 3 μm. The graphene oxide solution also includes aminopropyltriethoxysilane, and the mass fraction of aminopropyltriethoxysilane is 0.3%. The solvent of the graphene oxide solution is dimethyl sulfoxide, and ultrasonic treatment and stirring are carried out for 5 hours. The ultrasonic treatment frequency is 50 kHz, and the temperature during the stirring process is maintained at 70°C. After taking out and drying, graphene oxide / silicon dioxide composite particles are obtained, and the mass of graphene oxide in the obtained graphene oxide / silicon dioxide composite particles is 5 parts.
[0066] S2: 60 parts by weight of polypropylene masterbatch with a particle size of 0.1 mm was placed in a reactor, heated at a temperature of 165° C., the gas pressure in the reactor was 3.5 MPa, and the heating time was 1.5 h to obtain a polypropylene copolymer;
[0067] S3: adding the graphene oxide / silicon dioxide composite particles in S1, 12.5 parts by weight of polytetrafluoroethylene particles with a particle size of 10 μm, 2 parts by weight of aminopropyltriethoxysilane, 0.6 parts by weight of zinc stearate, 1 part by weight of dibenzylidene sorbitol and 1 part by weight of calcium stearate into a reactor, the reaction temperature is 325° C., the reactor pressure is 0.9 MPa, the reaction time is 5 hours, and a polypropylene mixed material is obtained;
[0068] S4: The polypropylene mixed material in S3 is first stretched at low temperature for 5 minutes and then stretched at high temperature for 12 minutes. The low temperature stretching temperature is 70°C and the high temperature stretching temperature is 140°C. The stretching directions of the low temperature stretching and the high temperature stretching are consistent. The stretching ratio during low temperature stretching is 1:2.5 and the stretching ratio during high temperature stretching is 1:6. After stretching, heat setting is performed at a heat setting temperature of 120°C and a heat setting time of 11 minutes to obtain a highly wear-resistant transparent MOPP composite label film substrate.
[0069] Embodiment 3
[0070] This embodiment prepares a highly wear-resistant transparent MOPP composite label film substrate, and the preparation process is as follows:
[0071] S1: 12.5 parts by mass of silicon dioxide particles with a particle size of 450 nm are sprinkled into a graphene oxide solution, wherein the mass fraction of graphene oxide in the graphene oxide solution is 2%, and the particle size of graphene oxide is 3 μm. The graphene oxide solution also includes aminopropyltriethoxysilane, and the mass fraction of aminopropyltriethoxysilane is 0.3%. The solvent of the graphene oxide solution is dimethyl sulfoxide, and ultrasonic treatment and stirring are carried out for 5 hours. The ultrasonic treatment frequency is 50 kHz, and the temperature during the stirring process is maintained at 70°C. After taking out and drying, graphene oxide / silicon dioxide composite particles are obtained, and the mass of graphene oxide in the obtained graphene oxide / silicon dioxide composite particles is 5 parts.
[0072] S2: 65 parts by weight of polypropylene masterbatch with a particle size of 0.1 mm was placed in a reactor, heated at a temperature of 165° C., the gas pressure in the reactor was 3.5 MPa, and the heating time was 1.5 h to obtain a polypropylene copolymer;
[0073] S3: adding the graphene oxide / silicon dioxide composite particles in S1, 12.5 parts by weight of polytetrafluoroethylene particles with a particle size of 10 μm, 2 parts by weight of aminopropyltriethoxysilane, 0.6 parts by weight of zinc stearate, 1 part by weight of dibenzylidene sorbitol and 1 part by weight of calcium stearate into a reactor, the reaction temperature is 325° C., the reactor pressure is 0.9 MPa, the reaction time is 5 hours, and a polypropylene mixed material is obtained;
[0074] S4: The polypropylene mixed material in S3 is first stretched at low temperature for 5 minutes and then stretched at high temperature for 12 minutes. The low temperature stretching temperature is 70°C and the high temperature stretching temperature is 140°C. The stretching directions of the low temperature stretching and the high temperature stretching are consistent. The stretching ratio during low temperature stretching is 1:2.5 and the stretching ratio during high temperature stretching is 1:6. After stretching, heat setting is performed at a heat setting temperature of 120°C and a heat setting time of 11 minutes to obtain a highly wear-resistant transparent MOPP composite label film substrate.
[0075] Embodiment 4
[0076] This embodiment prepares a highly wear-resistant transparent MOPP composite label film substrate, and the preparation process is as follows:
[0077] S1: 12.5 parts by mass of silicon dioxide particles with a particle size of 450 nm are sprinkled into a graphene oxide solution, wherein the mass fraction of graphene oxide in the graphene oxide solution is 2%, and the particle size of graphene oxide is 3 μm. The graphene oxide solution also includes aminopropyltriethoxysilane, and the mass fraction of aminopropyltriethoxysilane is 0.3%. The solvent of the graphene oxide solution is dimethyl sulfoxide, and ultrasonic treatment and stirring are carried out for 5 hours. The ultrasonic treatment frequency is 50 kHz, and the temperature during the stirring process is maintained at 70°C. After taking out and drying, graphene oxide / silicon dioxide composite particles are obtained, and the mass of graphene oxide in the obtained graphene oxide / silicon dioxide composite particles is 5 parts.
[0078] S2: 70 parts by weight of polypropylene masterbatch with a particle size of 0.1 mm was placed in a reactor, heated at a temperature of 165° C., the gas pressure in the reactor was 3.5 MPa, and the heating time was 1.5 h to obtain a polypropylene copolymer;
[0079] S3: adding the graphene oxide / silicon dioxide composite particles in S1, 12.5 parts by weight of polytetrafluoroethylene particles with a particle size of 10 μm, 2 parts by weight of aminopropyltriethoxysilane, 0.6 parts by weight of zinc stearate, 1 part by weight of dibenzylidene sorbitol and 1 part by weight of calcium stearate into a reactor, the reaction temperature is 325° C., the reactor pressure is 0.9 MPa, the reaction time is 5 hours, and a polypropylene mixed material is obtained;
[0080] S4: The polypropylene mixed material in S3 is first stretched at low temperature for 5 minutes and then stretched at high temperature for 12 minutes. The low temperature stretching temperature is 70°C and the high temperature stretching temperature is 140°C. The stretching directions of the low temperature stretching and the high temperature stretching are consistent. The stretching ratio during low temperature stretching is 1:2.5 and the stretching ratio during high temperature stretching is 1:6. After stretching, heat setting is performed at a heat setting temperature of 120°C and a heat setting time of 11 minutes to obtain a highly wear-resistant transparent MOPP composite label film substrate.
[0081] Embodiment 5
[0082] This embodiment prepares a highly wear-resistant transparent MOPP composite label film substrate, and the preparation process is as follows:
[0083] S1: 12.5 parts by mass of silicon dioxide particles with a particle size of 450 nm are sprinkled into a graphene oxide solution, wherein the mass fraction of graphene oxide in the graphene oxide solution is 2%, and the particle size of graphene oxide is 3 μm. The graphene oxide solution also includes aminopropyltriethoxysilane, and the mass fraction of aminopropyltriethoxysilane is 0.3%. The solvent of the graphene oxide solution is dimethyl sulfoxide, and ultrasonic treatment and stirring are carried out for 5 hours. The ultrasonic treatment frequency is 50 kHz, and the temperature during the stirring process is maintained at 70°C. After taking out and drying, graphene oxide / silicon dioxide composite particles are obtained, and the mass of graphene oxide in the obtained graphene oxide / silicon dioxide composite particles is 5 parts.
[0084] S2: 75 parts by weight of polypropylene masterbatch with a particle size of 0.1 mm was placed in a reactor, heated at a temperature of 165° C., the gas pressure in the reactor was 3.5 MPa, and the heating time was 1.5 h to obtain a polypropylene copolymer;
[0085] S3: adding the graphene oxide / silicon dioxide composite particles in S1, 12.5 parts by weight of polytetrafluoroethylene particles with a particle size of 10 μm, 2 parts by weight of aminopropyltriethoxysilane, 0.6 parts by weight of zinc stearate, 1 part by weight of dibenzylidene sorbitol and 1 part by weight of calcium stearate into a reactor, the reaction temperature is 325° C., the reactor pressure is 0.9 MPa, the reaction time is 5 hours, and a polypropylene mixed material is obtained;
[0086] S4: The polypropylene mixed material in S3 is first stretched at low temperature for 5 minutes and then stretched at high temperature for 12 minutes. The low temperature stretching temperature is 70°C and the high temperature stretching temperature is 140°C. The stretching directions of the low temperature stretching and the high temperature stretching are consistent. The stretching ratio during low temperature stretching is 1:2.5 and the stretching ratio during high temperature stretching is 1:6. After stretching, heat setting is performed at a heat setting temperature of 120°C and a heat setting time of 11 minutes to obtain a highly wear-resistant transparent MOPP composite label film substrate.
[0087] Embodiment 6
[0088] This embodiment prepares a highly wear-resistant transparent MOPP composite label film substrate, and the preparation process is as follows:
[0089] S1: 12.5 parts by mass of silicon dioxide particles with a particle size of 450 nm are sprinkled into a graphene oxide solution, wherein the mass fraction of graphene oxide in the graphene oxide solution is 2%, and the particle size of graphene oxide is 3 μm. The graphene oxide solution also includes aminopropyltriethoxysilane, and the mass fraction of aminopropyltriethoxysilane is 0.3%. The solvent of the graphene oxide solution is dimethyl sulfoxide, and ultrasonic treatment and stirring are carried out for 5 hours. The ultrasonic treatment frequency is 50 kHz, and the temperature during the stirring process is maintained at 70°C. After taking out and drying, graphene oxide / silicon dioxide composite particles are obtained, and the mass of graphene oxide in the obtained graphene oxide / silicon dioxide composite particles is 5 parts.
[0090] S2: 65 parts by weight of polypropylene masterbatch with a particle size of 0.1 mm was placed in a reactor, heated at a temperature of 165° C., the gas pressure in the reactor was 3.5 MPa, and the heating time was 1.5 h to obtain a polypropylene copolymer;
[0091] S3: adding the graphene oxide / silicon dioxide composite particles in S1, 12.5 parts by weight of polytetrafluoroethylene particles with a particle size of 10 μm, 2 parts by weight of aminopropyltriethoxysilane, 0.6 parts by weight of zinc stearate, 1 part by weight of dibenzylidene sorbitol and 1 part by weight of calcium stearate into a reactor, the reaction temperature is 325° C., the reactor pressure is 0.9 MPa, the reaction time is 5 hours, and a polypropylene mixed material is obtained;
[0092] S4: The polypropylene mixed material in S3 is first stretched at low temperature for 4 minutes and then stretched at high temperature for 12 minutes. The low temperature stretching temperature is 70°C and the high temperature stretching temperature is 140°C. The stretching directions of the low temperature stretching and the high temperature stretching are consistent. The stretching ratio during low temperature stretching is 1:2.5 and the stretching ratio during high temperature stretching is 1:6. After stretching, heat setting is performed at a heat setting temperature of 120°C and a heat setting time of 11 minutes to obtain a highly wear-resistant transparent MOPP composite label film substrate.
[0093] Embodiment 7
[0094] This embodiment prepares a highly wear-resistant transparent MOPP composite label film substrate, and the preparation process is as follows:
[0095] S1: 12.5 parts by mass of silicon dioxide particles with a particle size of 450 nm are sprinkled into a graphene oxide solution, wherein the mass fraction of graphene oxide in the graphene oxide solution is 2%, and the particle size of graphene oxide is 3 μm. The graphene oxide solution also includes aminopropyltriethoxysilane, and the mass fraction of aminopropyltriethoxysilane is 0.3%. The solvent of the graphene oxide solution is dimethyl sulfoxide, and ultrasonic treatment and stirring are carried out for 5 hours. The ultrasonic treatment frequency is 50 kHz, and the temperature during the stirring process is maintained at 70°C. After taking out and drying, graphene oxide / silicon dioxide composite particles are obtained, and the mass of graphene oxide in the obtained graphene oxide / silicon dioxide composite particles is 5 parts.
[0096] S2: 65 parts by weight of polypropylene masterbatch with a particle size of 0.1 mm was placed in a reactor, heated at a temperature of 165° C., the gas pressure in the reactor was 3.5 MPa, and the heating time was 1.5 h to obtain a polypropylene copolymer;
[0097] S3: adding the graphene oxide / silicon dioxide composite particles in S1, 12.5 parts by weight of polytetrafluoroethylene particles with a particle size of 10 μm, 2 parts by weight of aminopropyltriethoxysilane, 0.6 parts by weight of zinc stearate, 1 part by weight of dibenzylidene sorbitol and 1 part by weight of calcium stearate into a reactor, the reaction temperature is 325° C., the reactor pressure is 0.9 MPa, the reaction time is 5 hours, and a polypropylene mixed material is obtained;
[0098] S4: The polypropylene mixed material in S3 is first stretched at low temperature for 6 minutes and then stretched at high temperature for 12 minutes. The low temperature stretching temperature is 70°C and the high temperature stretching temperature is 140°C. The stretching directions of the low temperature stretching and the high temperature stretching are consistent. The stretching ratio during low temperature stretching is 1:2.5 and the stretching ratio during high temperature stretching is 1:6. After stretching, heat setting is performed at a heat setting temperature of 120°C and a heat setting time of 11 minutes to obtain a highly wear-resistant transparent MOPP composite label film substrate.
[0099] Embodiment 8
[0100] This embodiment prepares a highly wear-resistant transparent MOPP composite label film substrate, and the preparation process is as follows:
[0101] S1: 12.5 parts by mass of silicon dioxide particles with a particle size of 450 nm are sprinkled into a graphene oxide solution, wherein the mass fraction of graphene oxide in the graphene oxide solution is 2%, and the particle size of graphene oxide is 3 μm. The graphene oxide solution also includes aminopropyltriethoxysilane, and the mass fraction of aminopropyltriethoxysilane is 0.3%. The solvent of the graphene oxide solution is dimethyl sulfoxide, and ultrasonic treatment and stirring are carried out for 5 hours. The ultrasonic treatment frequency is 50 kHz, and the temperature during the stirring process is maintained at 70°C. After taking out and drying, graphene oxide / silicon dioxide composite particles are obtained, and the mass of graphene oxide in the obtained graphene oxide / silicon dioxide composite particles is 5 parts.
[0102] S2: 65 parts by weight of polypropylene masterbatch with a particle size of 0.1 mm was placed in a reactor, heated at a temperature of 165° C., the gas pressure in the reactor was 3.5 MPa, and the heating time was 1.5 h to obtain a polypropylene copolymer;
[0103] S3: adding the graphene oxide / silicon dioxide composite particles in S1, 12.5 parts by weight of polytetrafluoroethylene particles with a particle size of 10 μm, 2 parts by weight of aminopropyltriethoxysilane, 0.6 parts by weight of zinc stearate, 1 part by weight of dibenzylidene sorbitol and 1 part by weight of calcium stearate into a reactor, the reaction temperature is 325° C., the reactor pressure is 0.9 MPa, the reaction time is 5 hours, and a polypropylene mixed material is obtained;
[0104] S4: The polypropylene mixed material in S3 is first stretched at low temperature for 7 minutes and then stretched at high temperature for 12 minutes. The low temperature stretching temperature is 70°C and the high temperature stretching temperature is 140°C. The stretching directions of the low temperature stretching and the high temperature stretching are consistent. The stretching ratio during low temperature stretching is 1:2.5 and the stretching ratio during high temperature stretching is 1:6. After stretching, heat setting is performed at a heat setting temperature of 120°C and a heat setting time of 11 minutes to obtain a highly wear-resistant transparent MOPP composite label film substrate.
[0105] Embodiment 9
[0106] This embodiment prepares a highly wear-resistant transparent MOPP composite label film substrate, and the preparation process is as follows:
[0107] S1: 12.5 parts by mass of silicon dioxide particles with a particle size of 450 nm are sprinkled into a graphene oxide solution, wherein the mass fraction of graphene oxide in the graphene oxide solution is 2%, and the particle size of graphene oxide is 3 μm. The graphene oxide solution also includes aminopropyltriethoxysilane, and the mass fraction of aminopropyltriethoxysilane is 0.3%. The solvent of the graphene oxide solution is dimethyl sulfoxide, and ultrasonic treatment and stirring are carried out for 5 hours. The ultrasonic treatment frequency is 50 kHz, and the temperature during the stirring process is maintained at 70°C. After taking out and drying, graphene oxide / silicon dioxide composite particles are obtained, and the mass of graphene oxide in the obtained graphene oxide / silicon dioxide composite particles is 5 parts.
[0108] S2: 65 parts by weight of polypropylene masterbatch with a particle size of 0.1 mm was placed in a reactor, heated at a temperature of 165° C., the gas pressure in the reactor was 3.5 MPa, and the heating time was 1.5 h to obtain a polypropylene copolymer;
[0109] S3: adding the graphene oxide / silicon dioxide composite particles in S1, 12.5 parts by weight of polytetrafluoroethylene particles with a particle size of 10 μm, 2 parts by weight of aminopropyltriethoxysilane, 0.6 parts by weight of zinc stearate, 1 part by weight of dibenzylidene sorbitol and 1 part by weight of calcium stearate into a reactor, the reaction temperature is 325° C., the reactor pressure is 0.9 MPa, the reaction time is 5 hours, and a polypropylene mixed material is obtained;
[0110] S4: The polypropylene mixed material in S3 is first stretched at low temperature for 8 minutes and then stretched at high temperature for 12 minutes. The low temperature stretching temperature is 70°C and the high temperature stretching temperature is 140°C. The stretching directions of the low temperature stretching and the high temperature stretching are consistent. The stretching ratio during low temperature stretching is 1:2.5 and the stretching ratio during high temperature stretching is 1:6. After stretching, heat setting is performed at a heat setting temperature of 120°C and a heat setting time of 11 minutes to obtain a highly wear-resistant transparent MOPP composite label film substrate.
[0111] Comparative Example 1
[0112] This comparative example prepared a MOPP composite label film substrate, and the preparation process is as follows:
[0113] S1: 65 parts by weight of polypropylene masterbatch with a particle size of 0.1 mm was placed in a reactor, heated at a temperature of 165° C., the gas pressure in the reactor was 3.5 MPa, and the heating time was 1.5 h to obtain a polypropylene copolymer;
[0114] S2: 12.5 parts by weight of polytetrafluoroethylene particles with a particle size of 10 μm, 2 parts by weight of aminopropyltriethoxysilane, 0.6 parts by weight of zinc stearate, 1 part by weight of dibenzylidene sorbitol and 1 part by weight of calcium stearate are added into a reactor, the reaction temperature is 325° C., the reactor pressure is 0.9 MPa, the reaction time is 5 hours, and a polypropylene mixed material is obtained;
[0115] S3: The polypropylene mixed material in S2 is stretched at a stretching temperature of 140°C, a stretching time of 12 minutes, a stretching ratio of 1:6, and the stretching direction is always consistent during the stretching process. After stretching, heat setting is performed at a heat setting temperature of 120°C and a heat setting time of 11 minutes to obtain a MOPP composite label film substrate.
[0116] Samples of equal weight from Examples 1 to 9 and Comparative Example 1 were irradiated for 500 h in a UV aging test chamber, the haze was tested with reference to GB / T2410-2008, the samples were rotated 2000 times on a HT-1000 high temperature friction and wear tester, the mass loss was recorded, and the mass retention rate was calculated. The transparency and wear resistance were tested respectively. The test data are shown in Table 1.
[0117] Table 1 Abrasion resistance and transparency test data of Examples 1 to 9 and Comparative Example 1
[0118] Sample source Quality retention rate (%) Haze(%) Embodiment 1 89.4 2.1 Embodiment 2 92.6 1.6 Embodiment 3 95.6 1.3 Embodiment 4 95.1 1.5 Embodiment 5 93.6 2.2 Embodiment 6 92.4 1.5 Embodiment 7 98.2 1.1 Embodiment 8 96.3 1.2 Embodiment 9 93.5 1.4 Comparative Example 1 86.2 4.1
[0119] It can be seen from Table 1 that the quality retention rates in Examples 1 to 9 are all greater than the quality retention rate in Comparative Example 1, and the haze in Examples 1 to 9 is all less than the haze in Comparative Example. Therefore, a highly wear-resistant transparent MOPP composite label film substrate in the present application has superiority.
[0120] In Examples 1 to 5, as the mass ratio of polypropylene masterbatch in uniaxially stretched polypropylene gradually increases, the quality retention increases first and then decreases, and the haze decreases first and then increases. This is because as the mass ratio of polypropylene masterbatch increases, the overall crystallinity of the material may increase, resulting in an increase in the quality retention rate and an increase in wear resistance. When the proportion of polypropylene masterbatch is too high, excessive crystallization will occur, causing the intermolecular structure between the polypropylene material and the filler to become loose, resulting in a decrease in the quality retention rate and a decrease in wear resistance. Increasing the mass ratio of polypropylene masterbatch may help to improve the crystallinity of the material and the orderly arrangement of the molecular chains, thereby reducing light scattering and reducing the haze. When the proportion of polypropylene masterbatch is too high, the inhomogeneity between the polypropylene material and the filler increases, such as the generation of larger spherulites or other irregular structures, which will increase light scattering and increase the haze. The preferred embodiment is Example 3.
[0121] In Example 3 and Examples 6 to 9, as the low-temperature stretching time gradually increases, the quality retention first increases and then decreases, and the haze first decreases and then increases. This is because stretching can promote the arrangement and orientation of the molecular chains inside the material, improve the crystallinity and structural regularity of the material, thereby enhancing the thermal stability of the material, so that the quality retention rate is improved. Excessive stretching may cause damage to the internal structure of the material, such as excessive stretching and breaking of the molecular chains, which will reduce the thermal stability of the material and cause the quality retention rate to decrease. During the low-temperature stretching process, the arrangement and orientation of the molecular chains inside the material can reduce the microscopic defects and unevenness inside the material, thereby reducing light scattering, improving transparency, and reducing haze. Excessive stretching may cause the unevenness of the surface and internal structure of the material to increase, such as the generation of more micropores, cracks or other defects, which will increase light scattering and cause the haze to increase. The preferred embodiment is Example 7.
[0122] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A highly wear-resistant transparent MOPP composite label film substrate, characterized in that: include: Component A, component B and component C, of which: Component A is: polypropylene masterbatch; Component B includes: polytetrafluoroethylene particles, silicon dioxide and graphene oxide, wherein the mass ratio of the polytetrafluoroethylene particles, the silicon dioxide and the graphene oxide is: 15-20:15:20:5-10; Component C includes: a coupling agent, a lubricant, a nucleating agent and a stabilizer, wherein the mass ratio of the coupling agent, the lubricant, the nucleating agent and the stabilizer is: 4-8: 1-2: 3-5: 2-3; The mass ratio of the A component, the B component and the C component is 60-70:25-35:5-10.
2. The highly wear-resistant transparent MOPP composite label film substrate according to claim 1, characterized in that: The particle diameter of the polypropylene masterbatch is 0.1-1 mm, the particle diameter of the polytetrafluoroethylene particles is 0.1-10 μm, the particle diameter of the silicon dioxide is 400-500 nm, and the particle diameter of the graphene oxide is 2-4 μm.
3. The highly wear-resistant transparent MOPP composite label film substrate according to claim 1, characterized in that: The coupling agent is aminopropyltriethoxysilane, the lubricant is zinc stearate, the nucleating agent is dibenzylidene sorbitol, and the stabilizer is calcium stearate.
4. A method for preparing a highly wear-resistant transparent MOPP composite label film substrate, according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Sprinkle silica particles into graphene oxide solution, and stir for 4-6 hours by ultrasonic treatment, keep the temperature at 60-80°C during stirring, and take out and dry to obtain graphene oxide / silicon dioxide composite particles; S2: placing the polypropylene masterbatch into a reactor and heating it to 160-165° C. for 1-2 hours to obtain a polypropylene copolymer; S3: adding the graphene oxide / silicon dioxide composite particles, polytetrafluoroethylene particles, coupling agent, lubricant, nucleating agent and stabilizer in S1 into a reaction kettle, the reaction temperature is 320-330° C., the reaction time is 4-6 hours, and a polypropylene mixed material is obtained; S4: stretching and shaping the polypropylene mixed material in S3 to obtain a highly wear-resistant and transparent MOPP composite label film substrate.
5. The method for preparing a highly wear-resistant transparent MOPP composite label film substrate according to claim 4, characterized in that: The mass fraction of graphene oxide in the graphene oxide solution in S1 is 1-3%, the graphene oxide solution also includes a coupling agent, the mass fraction of the coupling agent is 0.1%-0.5%, and the solvent of the graphene oxide solution is dimethyl sulfoxide.
6. The method for preparing a highly wear-resistant transparent MOPP composite label film substrate according to claim 4, characterized in that: The frequency of the ultrasonic treatment in S1 is 40-60 kHz.
7. The method for preparing a highly wear-resistant transparent MOPP composite label film substrate according to claim 4, characterized in that: The gas pressure in the reactor in S2 is 3.4-3.6 MPa, and the gas pressure in the reactor in S3 is 0.8-1 MPa.
8. The method for preparing a highly wear-resistant transparent MOPP composite label film substrate according to claim 4, characterized in that: When stretching is performed in S4, low-temperature stretching is first performed for 5-7 minutes and then high-temperature stretching is performed for 10-15 minutes. The low-temperature stretching temperature is 60-80°C, and the high-temperature stretching temperature is 135-145°C. The stretching directions of the low-temperature stretching and the high-temperature stretching are consistent.
9. The method for preparing a highly wear-resistant transparent MOPP composite label film substrate according to claim 8, characterized in that: The stretching ratio during the low-temperature stretching is 1:2-3, and the stretching ratio during the high-temperature stretching is 1:5-7.
10. The method for preparing a highly wear-resistant transparent MOPP composite label film substrate according to claim 4, characterized in that: The heat setting temperature in S4 is 120° C., and the heat setting time is 10-12 minutes.
Citation Information
Patent Citations
Lithium ion battery membrane prepared by polypropylene mixture and preparing method thereof
CN102769115A
High-temperature resistant and wear-resistant styrene elastomer
CN109401177A
Novel polypropylene composite material and preparation method thereof
CN110669288A
High-pressure-resistant pipeline plastic and preparation method thereof
CN114369325A
High crystalline polypropylene microporous membrane, multi-component microporous membrane and methods for preparing same
CN1362892A